2023
DOI: 10.11591/ijece.v13i3.pp2812-2826
|View full text |Cite
|
Sign up to set email alerts
|

Pedestrian classification on transfer learning based deep convolutional neural network for partial occlusion handling

Abstract: <span lang="EN-US">The investigation of a deep neural network for pedestrian classification using transfer learning methods is proposed in this study. The development of deep convolutional neural networks has significantly improved the autonomous driver assistance system for pedestrian classification. However, the presence of partially occluded parts and the appearance variation under complex scenes are still robust to challenge in the pedestrian detection system. To address this problem, we proposed six… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…On the other hand, ResNet50 is a deep residual network that focuses on residual function learning, making it suitable for complex image recognition tasks [33]. The performance variation between MobileNet and ResNet50 in the context of PD classification aligns with research findings by Thu et al (2023), which showed that the pre-trained MobileNet outperformed ResNet50 in pedestrian classification [44].…”
Section: Discussionmentioning
confidence: 59%
“…On the other hand, ResNet50 is a deep residual network that focuses on residual function learning, making it suitable for complex image recognition tasks [33]. The performance variation between MobileNet and ResNet50 in the context of PD classification aligns with research findings by Thu et al (2023), which showed that the pre-trained MobileNet outperformed ResNet50 in pedestrian classification [44].…”
Section: Discussionmentioning
confidence: 59%
“…The pre-processed dataset will be a source for input into each CNN algorithm with various architectures, shown in Figure 4. There is the CNN algorithm with simple architectures [18], the CNN algorithm with a residual network-50 (ResNet50) architecture [19], [20], the CNN algorithm with a visual geometry group (VGG) 16 architecture [21], the CNN algorithm with convolutional neural networks for mobile vision applications (MobileNet) architecture [22] and CNN algorithm with an inception architecture [23]. Comparison graphically, the visualization CNN model architectures are simple architectures shown in Figure 4…”
Section: Modelingmentioning
confidence: 99%